Mental health difficulties among professional footballers <subtitle>A narrative review</subtitle> - Gary Woods; Thomas McCabe; Amit Mistry (Hogrefe AG, 2022)
Abstract. Introduction: In parallel with several current and former players' high-profile disclosures of psychological difficulties, academic studies published during the past decade have begun to examine the mental health of professional footballers. To date, a comprehensive review and critical analysis of these studies has yet to be conducted. Design: A narrative review of the literature was conducted following a Medline database search. Results: Thirteen studies were included in the review. A variety of mental health difficulties were explored, including depression, anxiety, distress, disordered eating, sleep disturbance and alcohol and substance use. Female players reported symptoms of common mental disorders more frequently than their male counterparts. Retired footballers reported increased rates of all mental health difficulties compared to active players. It is difficult to compare prevalence rates with both the general population and groups of other athletes due to the use of a variety of screening measures. Conclusion: The prevalence of symptoms of common mental disorders appears to be largely consistent with general population levels and in keeping with studies of other elite athlete groups, but further research is required to clarify this definitively. Injury and being retired were frequently associated with symptoms of common mental disorders, indicating that the screening and support of players during these vulnerable transitional periods may be of particular importance.